Impact of violence against women on severe acute maternal morbidity in the intensive care unit, including neonatal outcomes: a case–control study protocol in a tertiary healthcare facility in Lima, Peru. Issue 3 (14th March 2018) - Ayala Quintanilla, Beatriz Paulina; Pollock, Wendy E; McDonald, Susan J; Taft, Angela J
Abstract : Introduction: Preventing and reducing violence against women (VAW) and maternal mortality are Sustainable Development Goals. Worldwide, the maternal mortality ratio has fallen about 44% in the last 25 years, and for one maternal death there are many women affected by severe acute maternal morbidity (SAMM) requiring management in the intensive care unit (ICU). These women represent the most critically ill obstetric patients of the maternal morbidity spectrum and should be studied to complement the review of maternal mortality. VAW has been associated with all-cause maternal deaths, and since many women (30%) endure violence usually exerted by their intimate partners and this abuse can be severe during pregnancy, it is important to determine whether it impacts SAMM. Thus, this study aims to investigate the impact of VAW on SAMM in the ICU. Methods and analysis: This will be a prospective case-control study undertaken in a tertiary healthcare facility in Lima-Peru, with a sample size of 109 cases (obstetric patients admitted to the ICU) and 109 controls (obstetric patients not admitted to the ICU selected by systematic random sampling). Data on social determinants, medical and obstetric characteristics, VAW, pregnancy and neonatal outcome will be collected through interviews and by extracting information from the medical records using a pretested form. Main outcome will be VAW rate and neonatal mortality rate between cases and controls. VAW will be assessed by using the WHO instrument. Binary logistic followed by stepwise multivariate regression and goodness of fit test will assess any association between VAW and SAMM. Ethics and dissemination: Ethical approval has been granted by the La Trobe University, Melbourne-Australia and the tertiary healthcare facility in Lima-Peru. This research follows the WHO ethical and safety recommendations for research on VAW. Findings will be presented at conferences and published in peer-reviewed journals.